Organometallic and coordination clusters and polymers : syntheses and applications : London, Ontario, Canada, May 29-June 1, 2004 - Organometallic and Coordination Clusters and Polymers: Syntheses And Applications Symposium ( 2004 : London, Ontario, Canada); Abd-El-Aziz, Alaa S.; Harvey, Pierre Dominique, 1960- (Weinheim : Wiley-VCH, 2004)
42